2003
DOI: 10.1034/j.1601-5215.2002.51018.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Supplementation Therapy for Older Men: Potential Benefits and Risks

Abstract: Serum testosterone levels decline gradually and progressively with aging in men. Many manifestations associated with aging in men, including muscle atrophy and weakness, osteoporosis, reduced sexual functioning, and increased fat mass, are similar to changes associated with testosterone deficiency in young men. These similarities suggest that testosterone supplementation may prevent or reverse the effects of aging. A MEDLINE search was performed to identify studies of testosterone supplementation therapy in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(171 citation statements)
references
References 94 publications
(365 reference statements)
1
158
0
11
Order By: Relevance
“…63 Overviews of randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations report improvements in body composition with increased lean body mass and reduced fat mass, but limited benefit in physical capabilities and equivocal improvements in quality of life measures, including general well-being and fatigue. [64][65][66] However, the studies reported tend to be of limited size and duration, with a lack of large-scale trials with extended long-term follow-up. Thus, additional studies have been recommended incorporating vitality, well-being and/or quality of life as end points.…”
Section: Testosterone General Health and Quality Of Life In Aging Menmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Overviews of randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations report improvements in body composition with increased lean body mass and reduced fat mass, but limited benefit in physical capabilities and equivocal improvements in quality of life measures, including general well-being and fatigue. [64][65][66] However, the studies reported tend to be of limited size and duration, with a lack of large-scale trials with extended long-term follow-up. Thus, additional studies have been recommended incorporating vitality, well-being and/or quality of life as end points.…”
Section: Testosterone General Health and Quality Of Life In Aging Menmentioning
confidence: 99%
“…Trials of testosterone therapy generally have not been designed or adequately powered to detect effects on clinically significant cardiovascular events. 16,[64][65][66]119,120 Although randomized controlled trial data are lacking, there are observational data which support a relationship between low testosterone and fatal cardiovascular events. Lower testosterone levels have been associated with increased overall and cardiovascular-related mortality in middle-aged and older men.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 99%
“…This finding has fuelled many trials in the use of TRT as a possible treatment for sarcopenia. However, in E men, TRT reverses some but not all the effects of sarcopenia 17, 22. It is also associated with several side effects including an increase in the risk of developing prostate cancer and gynecomastia, alterations in the composition of plasma lipids, and increased cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, treating adult female rats,13 hypogonadal men,14 and E men with low testosterone (T) concentrations15 with T or any of its many derivatives for several weeks increases lean body mass and decreases fat content, suggesting that sex steroids are essential for the maintenance of skeletal mass and may be important in the management of sarcopenia. Although the concentration of free T in plasma decreases with age in both men and women,16 and T supplementation has been shown to increase lean body mass, T is not the most potent sex steroid in the body 17. Instead, in target tissues such as the skin, prostate, and brain, it is irreversibly metabolized to dihydrotestosterone (DHT) by the enzyme 5α‐reductase 18.…”
Section: Introductionmentioning
confidence: 99%
“…In hypogonadal men, testosterone replacement was associated with improved mood and well-being, and reduced fatigue and irritability [103][104][105]. Randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations, report equivocal improvements in QoL measures, including general well-being and fatigue [106,107]. For patients with major depression and/or dysthymia, improvement was equal to that achieved with standard antidepressants with significant improvement in the depression inventory score.…”
Section: Mood and Energy And Quality Of Life (Qol)mentioning
confidence: 99%